Online dating apps as a marketing channel - Rita, Paulo (2021)
Rita, P., Ramos, R. F., Moro, S., Mealha, M., & Radu, L. (2020). Online dating apps as a marketing channel: a generational approach. European Journal of Management and Business Economics, 30(1), 1-17. https://doi.org/10.1108/EJMBE-10-2019-0192